The influences of social media marketing on consumer purchase behaviour of low involvement product among generation y in sub-urban areas in Malaysia - Husin, Wann Huzida Roza (2019)
This study examined the influences of social media marketing (online communities, interaction, entertainment and perceived trust) and Generation Y online purchase behaviour of low involvement products in sub-urban areas. Additionally, the study also investigated the moderating effect of consumer engagement between social media marketing and Generation Y online purchase behaviour. The Uses and Gratification Theory was used in this study. A Survey Questionnaires was used to investigate online purchase made by Generation Y between ages 18-35 years old. A total of 384 questionnaires were distributed to Southern Region states namely Negeri Sembilan, Melaka and Johor. The data was analysed using Statistical Package for Social Science (SPSS) 23.0. All the variables were measured using five-point Likert scale. The study empirically proved that online communities, entertainment and perceived trust significantly and positively related to Generation Y online purchase behaviour. However, there was no relationship between interaction and Generation Y online purchase behaviour. Similarly, the moderating effect of consumer engagement was found to have no moderating effect. The study integrated Karman’s and Muda’s model and had adapted social media marketing dimensions which is online communities and interaction. Additionally, this study contributed to the inclusion of two new dimensions of social media marketing which are entertainment and perceived trust. Besides that, this study focused on sub-urban areas when many past studies concentrated on urban respondents. More importantly, this study assisted marketing managers to understand the Generation Y online purchase behaviour especially those resided in sub-urban areas. Furthermore, this study also has significant contribution to the government in understanding the technology and internet connectivity sites in sub-urban areas.